2011
DOI: 10.4047/jap.2011.3.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Resorption of labial bone in maxillary anterior implant

Abstract: PURPOSEThe purpose of this study was to evaluate the amount of resorption and thickness of labial bone in anterior maxillary implant using cone beam computed tomography with Hitachi CB Mercuray (Hitachi, Medico, Tokyo, Japan).MATERIALS AND METHODSTwenty-one patients with 26 implants were followed-up and checked with CBCT. 21 OSSEOTITE NT® (3i/implant Innovations, Florida, USA) and 5 OSSEOTITE® implants (3i/implant Innovations, Florida, USA) were placed at anterior region and they were positioned vertically at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
(23 reference statements)
0
30
1
2
Order By: Relevance
“…When an implant is placed in a more palatal position, a space is created between the implant and the buccal plate, allowing bone ingrowth from the surrounding interdental septa and from cranial more easily . To achieve optimal ridge preservation simultaneously with implant placement, research corroborated that a minimum thickness of at least 2 mm buccal hard tissue should be present . Retrospective results of our IIPP procedure revealed that, in case of application of a bovine substitute, the buccal crest thickness increased from 0.9 to 2.4 mm .…”
Section: Introductionmentioning
confidence: 80%
“…When an implant is placed in a more palatal position, a space is created between the implant and the buccal plate, allowing bone ingrowth from the surrounding interdental septa and from cranial more easily . To achieve optimal ridge preservation simultaneously with implant placement, research corroborated that a minimum thickness of at least 2 mm buccal hard tissue should be present . Retrospective results of our IIPP procedure revealed that, in case of application of a bovine substitute, the buccal crest thickness increased from 0.9 to 2.4 mm .…”
Section: Introductionmentioning
confidence: 80%
“…12,14 Significantly less implant failure was reported in the group with at least 2 mm of labial bone thickness. 15,16 The mean buccal bone thickness at 3 and 5 mm from the CEJ in canines, first premolars, and second premolars was below 2 mm. The frequency distribution of thick buccal bone wall at 3 mm from CEJ of the second premolar had the highest value (17.5%) when compared with that of canine (1.3%) and the first premolar (0.0%).…”
Section: Discussionmentioning
confidence: 99%
“…), while in a case series it was reported that buccal bone resorption extended to the apex in one‐third of 26 immediately placed implants (Cho et al. ).…”
mentioning
confidence: 99%
“…) still, only a handful of publications report on immediately placed implants (Cho et al. ; Degidi et al. ; Roe et al.…”
mentioning
confidence: 99%